2002
DOI: 10.1111/j.1151-2916.2002.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Electroplated Platinum Interlayer on the Morphology and Phases of Chemically‐Vapor‐Deposited Alumina on Single‐Crystal, Nickel‐Based Superalloy

Abstract: The feasibility of preparing a thin layer of α‐Al2O3 on the surface of a single‐crystal, Ni‐based superalloy was examined using a chloride‐based chemical vapor deposition (CVD) process previously developed for cutting tool applications. A coating directly deposited by this method on the alloy surface consisted of ∼1 μm α‐Al2O3 crystals in a matrix of amorphous Al2O3. When the alloy surface was predeposited with an electroplated Pt layer, the coating was mostly α‐Al2O3, but with the presence of fine microcracks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Also, the microcracks appearing on the TGO surface ( Figure 6(b)) could be attributed to the phase transformation of metastable Al 2 O 3 phases to the thermodynamically stable phase, ␣-Al 2 O 3 , as we have previously reported. [18,20] After 50 hours of oxidation, the classic duplex TGO microstructure was observed for this sample. It is known that there are three stages involved in an oxidation process: transient, steady, and breakaway stages.…”
Section: A Tgo Morphology Formed On Uncoated René N5mentioning
confidence: 99%
“…Also, the microcracks appearing on the TGO surface ( Figure 6(b)) could be attributed to the phase transformation of metastable Al 2 O 3 phases to the thermodynamically stable phase, ␣-Al 2 O 3 , as we have previously reported. [18,20] After 50 hours of oxidation, the classic duplex TGO microstructure was observed for this sample. It is known that there are three stages involved in an oxidation process: transient, steady, and breakaway stages.…”
Section: A Tgo Morphology Formed On Uncoated René N5mentioning
confidence: 99%
“…We have also previously observed whisker growth on a similar single-crystal Ni-based superalloy surface, unless the substrate was coated with a Pt interlayer. [11] Furthermore, we have recently observed that a very short preoxidation (ϳ1 minute) at 1050°C with a CO 2 ϩ H 2 gas mixture, prior to the CVD-Al 2 O 3 step, could be a practical way of significantly reducing the degree of whisker formation on the Ni-based superalloy surface. As we will report in this article, this observation motivated us to study (1) the effect of the CO 2 ϩ H 2 preoxidation on the surface nature of the single-crystal Nibased superalloy, and (2) the effect of this preoxidized layer on the nucleation and growth behavior of CVD ␣-Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%